Development of Project-Based Student Worksheets to Facilitate Learning Independence of Grade X Students at SMK Negeri 9 North Bengkulu - Ari Isnu Wibowo; Mariana Ade Cahaya; Hilyati Milla (Journal of Research in Social Science and Humanities, 2026)
This study aims to determine the validity level of project-based Student Worksheets (LKPD) and to identify the practicality level of project-based LKPD in facilitating the learning independence of Grade X students at SMK Negeri 9 North Bengkulu. This research employed a Research and Development (RD) method using the 4D model, which consists of four stages: define, design, develop, and limited disseminate. The research subjects were Grade X students of a vocational high school. The research instruments included expert validation sheets and response questionnaires distributed to teachers and students. The collected data were analyzed using descriptive quantitative techniques with percentage calculations to determine the level of validity and practicality of the developed product. The results of the study indicate that the project-based LKPD obtained an average validity score of 94.67%, which falls into the very valid category. In addition, the practicality test results show that the project-based LKPD achieved an average score of 89.79%, categorized as very practical. These findings demonstrate that the developed worksheets meet the criteria of content feasibility, clarity of presentation, and ease of use in the learning process. Furthermore, the implementation of project-based LKPD encourages students to participate actively in learning activities, complete tasks independently, and develop problem-solving skills through project-based tasks.Therefore, it can be concluded that the project-based LKPD is feasible and practical to be implemented in classroom learning and can effectively facilitate the development of students’ learning independence